(untitled) (Research, Society and Development, 2022)
The synthesis of ZSM-22 zeolite has been extensively studied due to its properties of form selectivity, acidity and hydrothermal stability, which is applied in important reactions in the areas of petroleum refining and petrochemicals. In view of this, the present work studied different approaches of synthesis of ZSM-22 using: 1-diaminohexane as a structure directing agent, (ii) methanol and seed crystals, (iii) aging of the synthesis gel with addition of polymer, surfactant and silane and (iv) starch, calcium carbonate and silanized silica with subsequent desilication. Thus, the effects of these methodologies on the textural properties, acidity and catalytic activity of the zeolites obtained were evaluated. The samples were characterized by X-ray diffraction (XRD), nitrogen adsorption-desorption, scanning electron microscopy (SEM), ammonia desorption at programmed temperature (NH3-TPD) and thermal analysis (TG/DTG). The catalytic activity and selectivity of the catalysts were evaluated in the model catalytic cracking reaction of n-heptane at 650 °C for 180 min. The synthesis route using methanol and seed crystals allowed obtaining ZSM-22 in 3 h of crystallization, drastically reducing the synthesis time compared to other methodologies. Despite this, the use of 1-diaminohexane led to the obtaining of zeolite with textural properties, acidity and catalytic activity superior to the other samples. The generation of mesoporosity was obtained through the use of silanized silica and subsequent desilication, leading to greater catalytic stability and less deactivation by coke. All catalysts showed similar selectivity to the formation of compounds in the range C2 to C4.